Pengaruh Struktur Modal dan Profitabilitas Terhadap Pajak Penghasilan Badan Non Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020 - Owen De Pinto Simanjuntak; Anggi Pratiwi Sitorus; Rodi Syafrizal (Jurnal EMT KITA, 2023)
The purpose of this study was to examine whether capital structure and profitability affect corporate income tax partially and simultaneously. This research is included in the quantitative research. The population of this study is non-manufacturing companies listed on the Indonesian Stock Exchange from 2017 to 2020, with a population of 370 people. The total sample consists of 17 companies, of which he made 68 observations over a four-year study period. Sampling by target sampling technique. The statistical method used is multiple linear regression analysis using SPSS version 25 to process the data. The analytical methods used include traditional acceptance tests including descriptive statistics, normality, multicollinearity, heteroskedasticity, autocorrelation, and decision and hypothesis tests. The results of this study show that capital structure has a partially positive and insignificant effect, profitability has a partially positive and significant effect, and at the same time the significant probability values ​​of capital structure and profitability are non-economic It has been shown to have a positive and significant effect on public interest. Manufacturing Corporate Income Tax IDX 2017-2020 Listed Companies.